LONTAR GAMA TIRTHA; PEMULIAAN AIR DALAM KONTEKS EKO-RELIGIUS - I Gede Sudiarta; Reland Udayana Tangkas (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2022)
Lontar Gama Tirtha is one of the Balinese literatures which has been inherited until now by Balinese people who believe in the position of water as a means of self-purification. Water has a very important position in the ecological system and is able to form ecosystems in the area of lakes, rivers, rice fields, and springs that are not only useful for daily needs but are also highly purified and functioned spiritually. Lontar Gama Tirtha explains the essence of water as a means of self-purification and a system of knowledge of water that is integrated with human beings. Lontar Gama Tirtha thoroughly explains the two water belief contexts that refer to the physical and spiritual aspects, namely "gama ning" and "gama cemer". The state of clear and cloudy water represents a state of self that is continuously purified from all impurities that are never separated from life. The context of the purification of water does not merely cleanse and purify the physical paradigm, but the strongest emphasis in that context is on the spiritual purification of the body, namely thoughts, words, and deeds.Keywords: Eco-Religious, water, Gama Tirtha